Carbon enriched thermal sprayed hard metal coatings used in PCD sintering - McKie, Amanda Lynne (My University, 2013)
During the sintering of fine grain (0.5μm) polycrystalline diamond (PCD) composite materials under high pressure-high temperature (HPHT) conditions, abnormal grain growth (AGG) of the diamond is observed at the diamond/substrate interface. These abnormally grown diamond particles can be several hundreds of microns in diameter and are major flaws in the material that can cause premature fail during application. Understanding of the mechanisms of grain growth in fine grained PCD can bring about ways to eliminate this defect. This project aimed to investigate the reduction of AGG diamond in 0.5μm diamond by changing the solubility of the infiltrating molten Co liquid used in PCD sintering. By increasing the carbon saturation level of the infiltrating Co melt, the chance for Ostwald ripening conditions of the diamond during sintering is reduced and AGG is eliminated. Modification of the carbon saturation within the Co melt can be achieved by carbon enriching the WC-Co substrate. Carbon enrichment can be achieved by carbon enriching a WC-Co powder and then HVOF thermal spraying it onto a WC-Co substrate. Results showed that carbon enrichment of coatings (2-6wt%C) was possible using a phenolic resin precursor followed by pyrolysis. Higher carbon contents added presented HVOF spraying problems; high free carbon burn off and lowered melting points which can lead to poor spraying and lower deposition rates. Carbon enrichment of WC-Co powders was also thought to potentially reduce undesirable eta phase generation during thermal spraying and thus result in an improvement in the wear resistance of the coatings on metal substrates (mild steel). These tests were performed and showed that eta phase generation can to be suppressed during thermal spraying of the carbon enriched powders. Wear resistance and hardness effects on the carbon enriched coatings before and after annealing heat treatment were also analysed and good results were obtained but contradictory is some cases when compared to other authors. Overall, 2wt%C samples showed the most improved properties in terms of WC and eta phase suppression and improved wear resistance, although at the expense of hardness. Another method of carbon enrichment was by using a graphite/diamond enhanced carbide (GDEC) interlayer. Both methods were analysed in this project. Carbon coatings were determined not to be very effective in eliminating AGG of fine grain diamond due to limited retained carbon in the coatings to sufficiently saturate the infiltrating melt. GDEC substrates on the other hand show a better possibility, a full 10vol.% GDEC was proved to suppress AGG formation at the diamond/substrate interface of 0.5μm diamond PCD. Alternatively, the reduction of AGG in fine grain diamond can also be eliminated by changing the interfacial energy of the diamond during sintering; this could be achieved by addition of a grain growth inhibitor. This project investigated the potential of a strong carbide former such as VC as a grain growth inhibitor in fine grain diamond. Addition of 2wt%VC proved to be sufficient to modify the interfacial energy to suppress AGG grain growth of fine (0.5μm) diamond. A model was developed comparing the grain growth mechanisms within a conventional carbide substrate and a carbon enriched substrate (coating or GDEC). Both grain growth of the diamond and formation of Co pool formation were discussed.